COMMUNICATION AND INTERACTIVE MARKETING MANAGEMENT THROUGH INTERNET ADVERTISING - Syahrial Shaddiq; Wuri Handayani (UPMI Management, 2021)
Internet advertising is a development of interactive online marketing communication media that marketers can choose from. The various advantages of internet advertising compared to traditional marketing communication media make this media increasingly used. Social networks or social media have the potential to help SMEs in marketing their products and services (Viral Marketing). Because it is able to reach large areas in a cost-effective manner. Through social networking, SME businesses can carry out marketing activities such as introducing products, establishing communication with customers and potential customers, and expanding business networks. And in its implementation also implements a Customer Relationship Management strategy.